APPLICATION OF DISCRIMINATION PROHIBITION IN THE LABOUR LAW OF THE SLOVAK REPUBLIC - Marcel Dolobáč (European Scientific Journal, ESJ, 2015)
In the first part of the submitted paper the author briefly describes antidiscrimination legislation in the Slovak Republic and its mutual correlation with the norms of the labour law. Simultaneously, the author points out the material nature of the prohibition of discrimination, the expression of which is the regulation of temporary positive action measures. In the second part of the article, the author contemplates the reasons for the absence of a case law of general courts in dealing with discriminatory conduct in employment relations, especially in regard to the tendencies of decision-making on claims from discriminatory conduct.